PRÁTICA PEDAGÓGICA EM TEMPOS DE PANDEMIA: UM ESTUDO SOBRE O ENSINO DAS HUMANIDADES NO COLÉGIO MILITAR DE SANTA MARIA - Junior, Ivan de Freitas Vasconcelos (2023)
This dissertation addressed issues related to pedagogical practice in the teaching of Humanities in times of the coronavirus (COVID-19) pandemic. Therefore, the work was based on authors such as: Rouanet (1987), Kenski (2012), Nussbaum (2015), Ordine (2016), Fava (2020), among others. The study problem was based on the following question: To what extent did the COVID-19 pandemic impact the pedagogical practice in the teaching of Humanities at Colégio Militar de Santa Maria (CMSM)? The objective was to analyze the impacts of the COVID-19 pandemic on the pedagogical practice of Humanities teachers at Colégio Militar de Santa Maria/RS. The research had a qualitative approach of the case study type, with methodological procedures based on documentary and bibliographical research. As for the procedures for data collection, information was collected within the scope of the CMSM through the application of a questionnaire to 8 (eight) professors of the Humanities disciplines (Geography, History, Philosophy and Sociology). As a result, a historical overview of the creation of military colleges and the presentation of the organizational and pedagogical structure of the CMSM were presented. It was verified that the CMSM curricular proposal is aligned with the vision of how the Brazilian Army understands the integral formation of the student (“the ideal student”) and the way of leading him to the job market. However, it is necessary to take a cautious look at the preparatory character that is being proposed in the curricular matrix, because by stimulating training focused on professional demands (job market), it ends up prioritizing Exact Sciences disciplines to the detriment of Human Sciences. The results also showed that the pandemic impacted the way teachers conduct pedagogical mediation, the way they carry out didactic planning, assessment activities carried out in remote environments, emotional behavior, and the level of engagement of students in school activities. It was concluded that the impacts caused by the pandemic on the pedagogical practice of research participants brought a series of challenges to teachers. Thus, the need for a constant review of teacher training policies was pointed out to overcome the educational challenges of the post-pandemic world. These training policies need to be re elaborated jointly by society, education professionals and public managers, listening carefully to everyone's demands. With the research, the need for continuous improvement of school management processes and teaching practices offered in the CMSM is evident, since they need to be aligned with the demands of 21st century education, providing the development of students' multiple intelligences and the appropriation of technological resources critically in school activities. In this sense, active teaching methodologies can contribute to teachers' pedagogical practices and help motivate and engage students.